Investigation of Normative Value of Commercialized Taiwan Smell Identification Test. (February 2021) - Hsieh, Ching-Hung; Chen, Philip G.; Zhou, Bing; Lin, Li-Jung; Lai, Jen-Tsung; Shen, Ping-Hung
Background: The Taiwan Smell Identification Test (TWSIT) was developed and successfully administered in Taiwanese population since 2015. However, for sanitation reason, the original liquid-jar form of this test is not appropriate. The commercialized TWSIT was then re-designed as "scratch-and-sniff" version: the TIBSIT (Top International Biotech, Taipei, Taiwan). This project aims to investigate the normative value of TIBSIT in different age groups and genders. Methods: Volunteers aged 20 to 80 with no subjective smell loss were recruited in a rhinology clinic. The participants were given full instructions on using the TIBSIT. Results: Two hundred and nine healthy subjects (female: male =107: 102) were enrolled into this study. The median TIBSIT score in female and male subjects is 47 and 46, respectively. Subjects were further divided into three age groups: (A) 20∼34 years (n = 77), (B) 35∼54 years (n = 77), and (C) 55∼80 years (n = 55). The TIBSIT scores at the tenth percentile value at each age group of male patients are 43, 42 and 37; while the scores at the tenth percentile value at each age group of female patients are 42, 42 and 41. TIBSIT score was significantly and inversely correlated with age (Spearman rho = − 0.20, p = 0.004.). Conclusion: We established the normative values of the new TIBSIT in different age groups in Taiwan. Future nation-wide screening is needed for more sophisticated norms establishment.